Green Industry Business Model Design for Naura Kitchen Business Using the Business Model Canvas Approach - Nur Aini Amazone; Yulianto Umar Rofii (BALANCE: Economic, Business, Management and Accounting Journal, 2026)
This study was conducted to design a green industry-based business model for Micro, Small, and Medium Enterprises (MSMEs) using the Business Model Canvas approach for Naura Kitchen. Waste is a significant issue in Bali Province. One of the waste-producing sectors is the home industry. Therefore, it is necessary to implement green practices in the MSME sector to reduce waste. The research method in this study uses a qualitative approach, grounded in the Business Model Canvas. Nine elements map the Naura Kitchen business model based on the green industry. The results of this study yield the concept of nine Business Model Canvas elements: main activities, primary resources, principal partners, distribution channels, customer relationships, customer segments, revenue streams, cost structures, and value propositions. This concept produces an overview of the implementation of the green industry in the Naura Kitchen business. The main activity in this business is the production of ecoprint colors from recycled materials